Computational and experimental study of thermal behavior in the oral cavity for biosensing applications - Yuanzhe Zhao; Jeroen H.M. Bergmann (Results in Engineering)
This study investigates transient heat transfer in the oral cavity under varying conditions using a finite element model combined with corresponding experiments. By modeling and measuring oral temperature during cold liquid intake, temperature recovery, and prolonged cold air inhalation, this study examines both temperature distribution across different oral regions and transient thermal dynamics. Results reveal that anterior teeth exhibit greater thermal sensitivity and slower temperature recovery following cold exposure, while posterior regions maintain higher and more stable temperatures. Additionally, buccal surfaces consistently show higher and more stable temperatures than lingual surfaces, underscoring the importance of measurement location for accuracy. The simulation demonstrated moderate agreement with experimental data, achieving a mean absolute error (MAE) of 3.39°C (13.46%) for upper facial positions and 2.91°C (10.35%) for lower facial positions during cold liquid intake scenarios. Furthermore, a strong correlation was observed between core body temperature and regional oral temperatures during prolonged cold air inhalation. While the total duration of mouth breathing significantly affects oral temperature, variations in respiratory cycle frequency showed minimal impact on thermal response. These findings provide important guidance for the development of non-invasive core temperature estimation methods based on oral biosensors. In particular, they offer insights for optimizing sensor placement in thermally stable regions and designing data-driven calibration algorithms capable of compensating for transient environmental disturbances, thereby enhancing the accuracy and reliability of wearable biosensing systems in dynamic conditions.